2000
DOI: 10.1111/j.1746-1561.2000.tb06473.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and Maintaining School‐Based Mental Health Services in a Large, Urban School District

Abstract: The Dallas (Texas) Public Schools established the first school-based health center in the United States in 1969. In 1993 a partnership between two school principals, a school mental health professional, and the medical director of the county mental health center was the impetus for the first comprehensive school-based mental health center in Texas. In 1995 the programs joined together as Youth and Family Centers (YFCs) to provide physical health, mental health, and other support services to students and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 7 publications
0
37
1
Order By: Relevance
“…For example, providing mental health services for students identified by SBHC staff as having high scores on measures of psychosocial impairment resulted in a 50% decrease in absences from school (Gall et al, 2000). Students in a large urban school district who received school-based mental health services had a 32% reduction in absences from school (Jennings, Pearson, & Harris, 2000). Students in an alternative high school who used the SBHC were absent less frequently than students who did not use the SBHC (McCord, Klein, Foy, & Fothergill, 1993).…”
Section: School-related Outcomesmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, providing mental health services for students identified by SBHC staff as having high scores on measures of psychosocial impairment resulted in a 50% decrease in absences from school (Gall et al, 2000). Students in a large urban school district who received school-based mental health services had a 32% reduction in absences from school (Jennings, Pearson, & Harris, 2000). Students in an alternative high school who used the SBHC were absent less frequently than students who did not use the SBHC (McCord, Klein, Foy, & Fothergill, 1993).…”
Section: School-related Outcomesmentioning
confidence: 90%
“…Another study found that students' involvement in SBHC services had a positive effect on the number of credits completed and on students' academic aspirations (Warren & Fancsali, 2000). Students in a large urban school district who received school-based mental health services had a 95% decrease in disciplinary referrals and a 31% decrease in failing course grades (Jennings et al, 2000). Similarly, school disciplinary referrals were decreased during a dropout prevention program run by an SBHC (Witt et al, 1999).…”
Section: School-related Outcomesmentioning
confidence: 96%
“…Alternative school students who used the services of a SBHC were twice as likely to stay in school and graduate than students who did not use the center (McCord, Klein, Foy, & Fothergill, 1993). Students in a large urban school district who received school-based mental health services had a 95% decrease in disciplinary referrals, a 31% decrease in failing course grades, and a 32% reduction in absences from school (Jennings, Pearson, & Harris, 2000).…”
Section: Academic Benefitsmentioning
confidence: 92%
“…27,[51][52][53] When mental health services are offered in SBHCs, students' access to mental health services is improved and communication is facilitated between students, school personnel, SBHC staff, and parents. 24,54,55 In Dallas, medical services decreased school absences by 50% among students who had 3 or more absences in a 6-week period, and students who received mental health services had an 85% decline in school discipline referrals. 55 In North Carolina, students who used SBHCs were significantly more likely to stay in school and to graduate or be promoted than did students who did not use SBHC services.…”
Section: Effectiveness Of Sbhcs In Improving Health Outcomesmentioning
confidence: 99%
“…24,54,55 In Dallas, medical services decreased school absences by 50% among students who had 3 or more absences in a 6-week period, and students who received mental health services had an 85% decline in school discipline referrals. 55 In North Carolina, students who used SBHCs were significantly more likely to stay in school and to graduate or be promoted than did students who did not use SBHC services. This was especially true for African American male students, who were 3 times more likely to stay in school.…”
Section: Effectiveness Of Sbhcs In Improving Health Outcomesmentioning
confidence: 99%